English: Power and Inequality in Social Practices - Zein Muchamad Masykur (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2024)
This paper critically considers tolerance as a most likely asymmetric concept that more often acts to underline social power imbalance than it is commonly perceived as serving diversity. For the qualitative literature study method, data were analyzed thematically from various sources of scholarly origin to disclose the underpinning power dynamics inherent in tolerance practices. Tolerance is demonstrated in the research to be practiced in highly selective ways, which put up a facade of inclusiveness while sustaining unjust power structures. Dominant groups use tolerance to make them look benevolent toward minorities while the processes and structures of inequality stay in place. In this respect, the distinction between passive tolerance—in which differences are merely condoned, not actively supported—and active tolerance—in which advocacy for and facilitation of minority rights can differ—can make an enormous difference in these power dynamics. Results provide evidence of a higher potential for meaningful social change with active tolerance compared with its passive counterpart.